Estética chicha: nuevas formas de creatividad popular en Lima de inicios del siglo XXI - Quispe Lázaro, Arturo (2021)
In Lima, new forms of artistic creation that come from the popular sphere have been produced since the beginning of the 21st century. Creations that come from the environment of Peruvian tropical music called chicha music. A significant first step was the change in the design and composition of the chicha poster, from advertising tropical music parties to one that conveyed ideas. In this way, it was connected with other popular and city spaces, becoming a diversity of creative proposals that were called chicha aesthetics. Why in a city like Lima, cosmopolitan, highly interconnected and globalized, does an artistic-cultural production of a popular nature emerge and generate impact from the environment of tropical chicha music? What characteristics does this aesthetic have and what relationship does it establish with ancestral culture in a highly interconnected context? These are some of the questions that we will address in this article, focused on Lima, the first two decades of this century. The methodology is inductive, we have selected a pictorial corpus of existing creations, finally we proposed a taxonomy that allowed us to analyze chicha aesthetics as contemporary artistic expression.